Palestinian Women's Rights and Global Advocacy: A Comprehensive Examination of Boycott Divestment and Sanctions Movement Strategies in 2010 - Sugianto, Heratri Anggrarini (HUMANISMA : Journal of Gender Studies, 2023)
The protracted conflict between Israel and Palestine has not ended, even though peace negotiations have been held several times, such as in 2010. As a result of this conflict, many Palestinian women lost their rights, and this attracted the sympathy of the world community, which then carried out the Boycott, Divestment, and Sanctions movement. This article aims to see the influence of this movement in advocating for the problems faced by Palestinian women at that time. The method used is to analyze various global society activities, reports, policies, and documents related to the Boycott, Divestment, and Sanctions movement in various parts of the world during 2010 using the Transnational Advocacy Networks (TANs) theory. The results show that during 2010, people in various parts of the world continuously carried out the Boycott, Divestment, and Sanctions movement, which demanded the return of the rights of Palestinians, including Palestinian women. Even though these movements did not end the conflict, they saw the mobilization of transnational networks to advocate for the rights of Palestinian women. This means that peace between Israel and Palestine is possible if the Boycott, Divestment, and Sanctions movement continues in global society.Konflik berkepanjangan Israel dan Palestina tak kunjung usai meskipun sudah berkali-kali diadakan perundingan perdamaian, seperti perundingan tahun 2010. Akibat konflik tersebut, banyak perempuan Palestina kehilangan hak mereka, dan hal ini menarik simpati masyarakat dunia yang kemudian melakukan gerakan Boycot Divestment and Sanctions. Artikel ini bertujuan untuk melihat pengaruh gerakan tersebut dalam mengadvokasi permasalahan yang dihadapi perempuan Palestina saat itu. Metode yang digunakan adalah dengan melakukan analisis terhadap berbagai kegiatan masyarakat global, laporan-laporan, kebijakan dan dokumen terkait dengan gerakan Boycot Divestment and Sanctions di berbagai belahan dunia selama tahun 2010 dengan memakai teori Transnational Advocacy Networks (TANs). Hasilnya menunjukkan bahwa selama tahun 2010 masyarakat di berbagai belahan dunia secara berkelanjutan melakukan gerakan Boycot Divestment and Sanctions yang menuntut pengembalian hak-hak warga Palestina tidak terkeceuali perempuan Palestina. Meskipun gerakan-gerakan tersebut tidak mengakhiri konflik yang terjadi, namun terlihat adanya mobilisasi jaringan transnasional dalam melakukan advokasi untuk memperjuangkan hak-hak perempuan Palestina. Ini berarti bahwa perdamaian antara Israel dan Palestina mungkin terjadi jika gerakan Boycot Divestment and Sanctions terus dilakukan masyarakat global.